Bottled water contaminant exposures and potential human effects. (January 2023) - Bradley, Paul M.; Romanok, Kristin M.; Smalling, Kelly L.; Focazio, Michael J.; Evans, Nicola; Fitzpatrick, Suzanne C.; Givens, Carrie E.; Gordon, Stephanie E.; Gray, James L.; Green, Emily M.; Griffin, Dale W.; Hladik, Michelle L.; et al.
Graphical abstract: Highlights: Bottled water (BW) consumption increasing, with public-supply drinking water concerns. Directly comparable, broad contaminant-mixture exposure assessments lacking for BW. 465 organics/53 inorganics/14 microbial indicators/1 bioactivity assessed in 30 BW. 48 inorganics/45 organics were detected, and benchmark screening levels were exceeded. Contaminant mixtures of potential human-health concern also common in BW. Abstract: Background: Bottled water (BW) consumption in the United States and globally has increased amidst heightened concern about environmental contaminant exposures and health risks in drinking water supplies, despite a paucity of directly comparable, environmentally-relevant contaminant exposure data for BW. This study provides insight into exposures and cumulative risks to human health from inorganic/organic/microbial contaminants in BW. Methods: BW from 30 total domestic US (23) and imported (7) sources, including purified tapwater (7) and spring water (23), were analyzed for 3 field parameters, 53 inorganics, 465 organics, 14 microbial metrics, and in vitro estrogen receptor (ER) bioactivity. Health-benchmark-weighted cumulative hazard indices and ratios of organic-contaminant in vitro exposure-activity cutoffs were assessed for detected regulated and unregulated inorganic and organic contaminants. Results: 48 inorganics and 45 organics were detected in sampled BW. No enforceable chemical quality standards were exceeded, but several inorganic and organic contaminants with maximum contaminant level goal(s) (MCLG) of zero (no known safe level of exposure to vulnerable sub-populations) were detected. Among these, arsenic, lead, and uranium were detected in 67 %, 17 %, and 57 % of BW, respectively, almost exclusively in spring-sourced samples not treated by advanced filtration. Organic MCLG exceedances included frequent detections of disinfection byproducts (DBP) in tapwater-sourced BW and sporadic detections of DBP and volatile organic chemicals in BW sourced from tapwater and springs. Precautionary health-based screening levels were exceeded frequently and attributed primarily to DBP in tapwater-sourced BW and co-occurring inorganic and organic contaminants in spring-sourced BW. Conclusion: The results indicate that simultaneous exposures to multiple drinking-water contaminants of potential human-health concern are common in BW. Improved understandings of human exposures based on more environmentally realistic and directly comparable point-of-use exposure characterizations, like this BW study, are essential to public health because drinking water is a biological necessity and, consequently, a high-vulnerability vector for human contaminant exposures.